Resolution of the Dual Certificate Issue in Makassar City through the State Administrative Court to Realize Legal Certainty (Case Study Decision No. 31 PK/TUN/2018) - Warsifah (International Journal of Science and Society, 2022)
The purpose of this study is to analyze the problem of dual certificates in the city of Makassar through the State Administrative Court to realize legal certainty. The research method used is normative juridical research, namely research on the application of law in society. The research was carried out in a juridical manner, meaning research that refers to existing literature studies or to secondary and normative data. The data obtained by the author from this literature review will be analyzed descriptively. Based on these considerations, in the opinion of the Supreme Court, there are sufficient reasons to grant the Cassation Petitioner from the Head of the Makassar City Land Office. Based on this, the Decision of the Makassar State Administrative High Court Number 93/B/2016/PT.TUN.MKS, dated 27 September 2016 which affirms the Makassar State Administrative Court Decision Number 68/G/2015/P.TUN.Mks. April 25, 2016 cannot be maintained and must be cancelled.